The Latest Trends VS Urban Environment - Bulgakova, Elena; Lidin, Konstantin (project baikal, 2019)
The notion of health is viewed as a degree of resistance of the human internal environment to external influences. The authors propose an idea of emotionally healthy urban environment that provides a wider and well-balanced emotional spectrum. The trend for one or another architectural style causes predominance of certain emotions and thus hinders formation of a healthy environment. The impact of trends is illustrated by means of an example of Leroy Merlin catalogues.